Efecto De Di`Ferentes Intensidades De Poda De FormaciÃ³n En El Crecimiento Inicial De Melina (Gmelina Arborea Roxb.) - Lara Vasconez, Norma Ximena; Cevallos, Eduardo; Almeida, Santiago; Lara, Sulema (European Scientific Journal, ESJ, 2016)
This research aims to evaluate the effect of different intensities of formation pruning in the initial development of the Melina (Gmelina arborea Roxb.) in the Pedro Vicente Maldonado canton located in the Pichincha Province. An established Melina (beech wood) plantation, with three different intensities of pruning were used; the experimental design utilized 3 pruning treatments on randomized complete blocks and the control plot, 4 repetitions with a total of 16 experimental units, the investigation began at 3 months after planting and finished when they were 8 months old. The results being that the best diameter was obtained with the pruning of 60% of the tree, the height didn't have any significant statistical difference between treatments, the best straightness was obtained with 50% and 70% pruning, the highest number of branches pruned were pruned 70%, the control tree has the biggest number of broken off branches. The conclusion being that the best increments in diameters were obtained by the control plot; however, this pruning treatment is rejected because the purpose is to obtain wood free of knots. Without taking into consideration the control plot, the best diameters were obtained by pruning 60%, but the form of the tree trunk presents a slight curve in relationship to the intensity of pruning 50% and 70%, where the trees are straighter but with smaller diameters. The formation pruning doesnâ€™t influence the height growth of the plant, but it is positive in the increment of the diameter and the straightness. The lack of pruning in the Gmelina causes the breaking off of branches causing damage to the trunk of the tree.